2020
DOI: 10.1101/2020.02.11.944272
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryopreservation of midbrain dopaminergic neural cells differentiated from human embryonic stem cells

Abstract: Recent advancements in protocols to differentiate human pluripotent stem cells into midbrain dopaminergic (mDA) neurons has improved the ability to model Parkinson's disease (PD) in a dish, and has provided a scalable source of donor cells for emerging PD cell replacement therapy (CRT). However, to facilitate reproducibility, collaboration, and clinical trials it would be highly beneficial to cryopreserve committed mDA neural precursors cells in a ready-to-use format. In terms of cell manufacturing for PD CRT … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Another study reported the cryopreservation of primary mouse motor neurons in DMSO and post-thaw cell recovery rate of 68.8% ( Parker et al, 2018 ). There were two accounts of cryopreserved dopaminergic progenitors and neurons derived from hiPSCs and human embryonic stem cells (hESCs), with the highest reported post-thaw recovery approaching 50% upon 24-h treatment in apoptosis inhibitors ( Wakeman et al, 2017 ; Drummond et al, 2020 ). In comparison, the present study demonstrated DMSO-free cryopreservation of neuronal cells, with post-thaw survival of D5 crest measured at 91.6% immediately post-thaw, 88.2% 24 h post-thaw, and of D7 SN measured at 93.6% immediately post-thaw, 84.1% 24 h post-thaw, all of which were significantly higher than 50% ( p < 0.05) even without the use of apoptosis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported the cryopreservation of primary mouse motor neurons in DMSO and post-thaw cell recovery rate of 68.8% ( Parker et al, 2018 ). There were two accounts of cryopreserved dopaminergic progenitors and neurons derived from hiPSCs and human embryonic stem cells (hESCs), with the highest reported post-thaw recovery approaching 50% upon 24-h treatment in apoptosis inhibitors ( Wakeman et al, 2017 ; Drummond et al, 2020 ). In comparison, the present study demonstrated DMSO-free cryopreservation of neuronal cells, with post-thaw survival of D5 crest measured at 91.6% immediately post-thaw, 88.2% 24 h post-thaw, and of D7 SN measured at 93.6% immediately post-thaw, 84.1% 24 h post-thaw, all of which were significantly higher than 50% ( p < 0.05) even without the use of apoptosis inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Jennifer Colquhoun for artwork in Figure 2, and Prof. David Melton for critical comments in the study. This manuscript has been released as a pre-print at bioRxiv (Drummond et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%